Peer‐to‐Peer Family Navigators in Primary Care: Enhancing Child Mental Health Outcomes. (20th August 2020) - Grimes, K.; Creedon, T.; Cook, B.
Abstract : Research Objective: Only 1 in 5 US children with a psychiatric or substance use disorder receives treatment. To investigate the impact of pediatric integrated care, including peer‐to‐peer family support, on identification and engagement of children in an urban safety‐net system. Study Design: We conducted a prospective, non‐randomized trial comparing clinical functioning and health services utilization outcomes between youths receiving CPM and those receiving usual care. Youths were referred by their pediatricians for child psychiatry evaluation. Each youth's family was given the option to participate in the 12‐month study following evaluation. Follow‐up observations take place at 6 and 12 months following baseline. Study participants received a multi‐disciplinary, integrated care team evaluation, including peer‐to‐peer parents in the primary care clinic. Claims and electronic medical record data provide information on utilization. We used propensity score weights to balance participants on baseline characteristics and estimated multivariate generalized estimating equations with a difference‐in‐differences framework to produce doubly‐robust estimates of relative pre‐post changes for CPM vs. usual care accounting for clustering of observations within participants. Population Studied: In the highly diverse population served by this urban safety‐net system, barriers such as stigma, language, and geography create access disparities. Study sample = 171 CPM youth and 290 Controls. All were primary care pediatric patients ages 2 to 17. CPM youth mean age = 10 years; 48.54% identify as female. Study sample families earn <35 000 a year; over 50 % speak a primary language other than English. Most frequent Diagnosis is Anxiety (39%) for CPM and Depression (33%) for Controls. Childhood trauma: 64% of CPM youth have 3+ ACEs. Principal Findings: Race/Ethnicity: 60.8% of our sample identify as Latinx, 17.0% as non‐Hispanic white, and 16.4% as non‐Hispanic Black/African American. ED Utilization drops 58% from baseline to 6 mos. for CPM youth, compared with 4% decline for controls ( P < 0.026). Outpatient MH utilization triples ( P = 0.002) for CPM use and doubles ( P < 0.001) for controls, at 6 mos. Clinical functioning is assessed via two separate standardized measures (CGAS and CAFAS) and statistically significant change from baseline to 6 mos. is found on both measures. Self‐Harm/Lethality scale showed an average improvement of 71% from baseline to 6 mos. post. Study retention was 88% at 6 months. Conclusions: Emerging evidence indicates improved child mental healthcare outcomes are possible for youth with access and engagement barriers, through the introduction of integrated parent support and child psychiatry consultation within familiar pediatric settings. Implications for Policy or Practice: These early findings suggest that the Collaborative Practice Model has the potential to improve child mental healthcare access and engagement rates in populations at‐risk for disparities. If further study supports these findings, the effect of early engagement could lead to reduced time to treatment; this, in turn, has the potential to lessen the morbidity burden of childhood trauma or emerging mental illness. If the CPM approach can even partially offset access disparities and support treatment engagement, there is an opportunity to shift service use from more restrictive settings to home and community‐based care. Primary Funding Source: SAMHSA.